Non-thermoregulatory modulation of sweating in humans - Shibasaki, M.; Kondo, N.; Crandall, G. (Exercise and Sport Sciences Reviews, 2003)
Sweating in humans is critical for appropriate thermoregulation during exercise and/or exposure to warm environmental temperatures. In addition to thermal controllers of sweating, a number of non-thermal factors modulate the sweating response. This review summarizes the primary non-thermal neural modifiers of sweating in humans.